I am not awake but I cannot sleep : [a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts, Massey University - Bolland, Toni (Massey University, 2003)
Last year my father became very ill. After having a number of strokes, his mental and physical capacity became diminished to the extent that he was no longer able to communicate or move about, and he was hospitalised. On the 8th of May this year he died. My father's inability to communicate had a profound effect on me. It was almost as though communication meant life and I grieved then as if he had died already. When he did die eight months later, I had already begun to use my work to investigate concepts of in-between-ness and paradox. In the personal sense, my father was representative of a known and quantifiable reality - a reference point from which I had developed understandings and meanings about my identity and place in the world. His illness turned my certainties into uncertainties. Trying to find a point of reference in the midst of such an experience was difficult. Relative spaces tended to shift. I likened it to trying to focus my eyes on a blurred image, or listening to tuneless sound and straining to hear a familiar melody. This experience strongly sharpened my conceptual skills. Dealing with ephemera and uncertainty pushed me to find a focus (locus?) and alongside was an opportunity to really explore materiality and process. In November I presented what I knew was good work but was unable to write about it coherently or articulate it clearly, and I was confused about the issues that had surfaced.
Keywords: Uncertainty in art; Art installations; Communication in art